Relationship of MicroRNAs with Transposable Elements in the Type 1 Diabetes Development - R. N. Mustafin (Архивъ внутренней медицины)
The review article describes the involvement of epigenetic factors in type 1 diabetes mellitus (T1DM) etiopathogenesis. The disease is characterized by changes in expression of microRNAs that affect the transcription of genes involved in autoimmune reactions, destruction of beta cells and insulin production. However, the cause of the observed epigenetic changes is still unclear. In evolution, the sources of microRNA genes are transposable elements, which occupy up to 45 % of the entire human DNA sequence and are drivers of epigenetic regulation in ontogenesis. They are sources of transcription factor sequences and binding sites for them. Features of the genome distribution of transposable elements can cause changes in the number of 5’VNTR (variable number of tandem repeats) — repeats of insulin promoter region and HERV insertions into HLA genes, which affects their expression. Therefore, I assume that the cause of the development of type 1 diabetes mellitus may be an imbalance in transcription activation of transposons, which contributes to changes in the expression of specific microRNAs and protein-coding genes, and also contributes to autoimmune response development. Triggers for this may be individual features of genome distribution of transposons, viral infections and stress. An analysis of the scientific literature confirms my proposed mechanisms for T1DM development, since the global role of retroelements in hormonal regulation, the sensitivity of transposable elements to exogenous viral infections and stress, and HERV-W expression of the majority of patients with T1DM with activation of the autoimmune response have been proven. Analysis of the MDTE DB (miRNAs derived from transposable elements database) database showed the transposon origin of 12 T1DM-associated microRNAs (miR-192, miR-224, miR-31, miR-320c, miR-326, miR-340, miR-342, miR-44661, miR-548c, miR-652, miR-95), the use of which can become the basis for targeted therapy for T1DM.